Evaluation of Sustainable Development of Tourism Cities Based on SDGs and Tourism Competitiveness Index: Analysis of 221 Prefecture-Level Cities in China - Junli Gao (MDPI AG, 2021)
Based on the Sustainable Development Goals and competitiveness index, an evaluation index system for sustainable development of tourism cities was established. The sustainable development level of 221 outstanding tourism cities in 2018 was evaluated, and their sustainable development paths were designed accordingly. The results show the following: (1) There is a large gap in sustainable development scores. In general, no city has achieved a strong sustainable development model. Natural and cultural resources and protection systems are the shortcomings of the systems. (2) The weights of natural and cultural resources and protection systems are the largest, and the weights of natural and cultural resources endowment, degree of tourism infrastructure construction, and economic support for natural and cultural resources are larger. Nature reserve coverage index, network popularity, and other indicators have greater weight. (3) There is a gap in the sustainable development level of tourism cities in the eight comprehensive economic zones. The economic zones in the eastern and southern coastal areas are better than those in the northwest and the middle reaches of the Yellow River. (4) The driving factors of the eight types of tourism cities distinguished by their characteristics are basically the same, but the obstacles are different.